Active labor market programs: Employment gain or fiscal drain? - Alessio J. G. Brown; Johannes Koettl (IZA Journal of Labor Economics, 2015)
This paper provides a new perspective by classifying active labor market programs (ALMPs) depending on their objectives, relevance and cost-effectiveness during normal times, a crisis and recovery. We distinguish ALMPs providing incentives for retaining employment, incentives for creating employment, incentives for seeking and keeping a job, incentives for human capital enhancement and improved labor market matching. Reviewing evidence from the literature, we discuss especially indirect effects of various interventions and their cost-effectiveness. The paper concludes by providing a systematic overview of how, why, when and to what extent specific ALMPs are effective.
Keywords: J08; J22; J23; J38; E24; 330; Active labor market programs; Short work; Subsidies; Training; Workfare; Activation; Sanctions; Job search assistance; Intermediation; Counseling; Cost- effectiveness